Why won't task conflict cooperate? Deciphering stubborn results. Issue 4 (7th October 2014) - A Posthuma, Richard; L. Loughry, Misty; C. Amason, Allen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to suggest why the theoretically positive relationship between task conflict and team performance has received mixed empirical support. Design/methodology/approach – We review the literature on task conflict and offer explanations for findings that contradict the expected positive relationship between task conflict and team performance. Findings – High levels of correlation among task, relationship and process conflict, and measurement and data analysis issues make it difficult to isolate the effects of each type of conflict. Group-level moderators, including values congruence, goal alignment, norms for debate and the group's performance history and conflict history affect the relationship between task conflict and performance. The complex relationship between conflict and trust may cause task conflict to have mixed effects on performance. Individual differences and conflict management approaches also affect the relationship between task conflict and performance. Temporal issues and stages of group development are other relevant influences. Practical implications – To better achieve the theorized performance benefits of task conflict, a context characterized by trust is needed. Then norms fostering task conflict can be cultivated and employees can be trained in conflict management. Individual differences that affect team members' ability to confidently accept task conflict can be considered in selection. Originality/value – Suggestions are presented for future research that may explain discrepant findings in the past empirical literature. In particular, it may be difficult for some team members to perceive task conflict in well-functioning teams. Measures of task conflict that avoid the use of words with a negative connotation should be tested.